2012
DOI: 10.3109/09593985.2012.698718
|View full text |Cite
|
Sign up to set email alerts
|

Low impact weight-bearing exercise in an upright posture increases the activation of two key local muscles of the lumbo-pelvic region

Abstract: To date, a range of exercises have been used to improve the function of the lumbar multifidus (LM) and transversus abdominis (TrA) muscles in people with low back pain, but uncertainty remains as to what exactly constitutes meaningful LM and TrA training. We examined the effects of exercising with a new device which combines weight-bearing, an unstable base of support (BOS) (feet), an upright posture with a relatively stable lumbo-pelvic area, and functional lower limb movement, with the aim of exploring which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…In the present study, the computed model activities of lumbo-pelvic muscles during FRED exercise are in line with previous physiological studies [10,14] and reinforce the findings that the combination of lower-limb movement and weight-bearing in a constant and slow motion shows great potential to activate these muscles [7,10,14]. The results from the FRED oneG model indicated that all of the investigated lumbo-pelvic muscles are constantly activated throughout the whole exercise cycle.…”
Section: Model Validation and Fred Onegsupporting
confidence: 78%
See 3 more Smart Citations
“…In the present study, the computed model activities of lumbo-pelvic muscles during FRED exercise are in line with previous physiological studies [10,14] and reinforce the findings that the combination of lower-limb movement and weight-bearing in a constant and slow motion shows great potential to activate these muscles [7,10,14]. The results from the FRED oneG model indicated that all of the investigated lumbo-pelvic muscles are constantly activated throughout the whole exercise cycle.…”
Section: Model Validation and Fred Onegsupporting
confidence: 78%
“…Previous terrestrial studies with the FRED reported promising results, indicating that it could be a valid tool to be used in people with deficits of deep spinal and 'anti-gravity' muscles [7,10,14]. In the present study, the computed model activities of lumbo-pelvic muscles during FRED exercise are in line with previous physiological studies [10,14] and reinforce the findings that the combination of lower-limb movement and weight-bearing in a constant and slow motion shows great potential to activate these muscles [7,10,14].…”
Section: Model Validation and Fred Onegmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Debuse et al (2013) investigated a new exercise device, the Functional Re-adaptive Exercise Device (FRED) (Figure 1), that has been designed to recruit the LM and TrA muscles. FRED exercise requires the user to perform slow controlled cyclical movement of the feet against no external resistance, necessitating active control of motion by both legs .…”
Section: Introductionmentioning
confidence: 99%